Wanita Dan Belanja : Aspek Motivasi Dilihat Dari Sudut Pandang Perilaku Konsumen - Nuri Purwanto (Universitas Islam Balitar, 2021)
This study aims to find and explain the underlying motives of women, especially mothers of Generation Y in shopping activities. The method used in this research is qualitative with a case study approach. The informants of this study were 2 women aged 26 to 41 years (1980-1995). Data collection techniques with in-depth interviews, observation and documentation. Data analysis used the Miles and Huberman model and tested by source triangulation and theoretical triangulation. The results showed that consumers' shopping motives, especially Generation Y mothers, had different shopping motives. There are several shopping motives, namely utilitarian shopping motives, hedonic shopping motives, product shopping motives, time shopping motives, place shopping motives and mood shopping motives. In this study it was also found that the dominant factor for mothers in shopping activities aimed at satisfying the emotional aspect. The findings of this study are the desire and the streets in shopping activities.